Secondary Victimization in the Official Duties of Police Officers - Kulmukhanbetova, B.A.; Dyusebekova, S.B. (Bulletin of the Karaganda University “Law Series”, 2026)
The relevance of the study is determined by the insufficient regulatory and organizational protection of police officers exposed to secondary victimization in the course of their professional activities. The purpose of the study is to identify the features of secondary victimization and to assess the effectiveness of existing prevention mechanisms within the system of internal affairs bodies of the Republic of Kazakhstan. The object of the study is the public relations arising from internal investigations involving police officers. The study employs methods of systematic analysis of scientific literature, examination of regulatory legal acts, and an empirical study in the form of a survey of police officers. The results indicate the fragmented nature of preventive practices and a high demand among police officers for formalized protection guarantees. The conclusions substantiate the need to improve legal regulation and introduce specific mechanisms to protect police officers. Implementing specialized protection procedures will increase officers’ trust in internal investigations.